The surgical management of peripheral IV extravasation injuries in infants and children - Genevieve Kierulf; Nicole Becher; Adam Goldsmith; Young Mee Choi; Steven Moulton (Elsevier, 2024)
Introduction: Peripheral IV extravasation (PIVE) injuries are a common cause of skin injury in infants and children. Although most PIVE injuries are minor and self-limited, severe PIVE injuries associated with calcium deposition and/or full-thickness skin injury will require surgical management. Methods: This is a retrospective review of children with PIVE injures who required surgical management at our institution from 2012 to 2022. Data collected included demographics, substance infiltrated, immediate management, surgical history, and long-term outcomes. Immediate management for those at imminent risk for skin loss or circulation impairment involved treatment with hyaluronidase to minimize tissue damage, followed by removal of the IV catheter. PIVEs involving calcium containing infiltrates were observed for 2-4 weeks to allow the calcium to precipitate, before undertaking surgical debridement of calcium deposits. Results: There were 11 PIVE injuries requiring surgery during the 10-year study period, of which 7 (63.6 %) were infants (< 30 days old). Surgery was delayed 2-4 weeks for those whose infiltrate contained calcium, to allow for precipitation and coalescence of the calcium in the soft tissue. Nine patients required debridement with skin grafting. One patient underwent debridement with wound closure, and one underwent needle decompression alone. Eight patients (72.7 %) received follow-up from OT/PT services, and most (75 %) achieved optimal functional outcomes including full range of motion and age-appropriate motor skills. Conclusions: Most IV infiltrate injuries self-resolve with no sequelae. Those injuries caused by calcium containing fluids or caustic medications can result in significant tissue destruction requiring operative intervention. Level of Evidence: Treatment Study, Level IV